Managing the Crisis in Iceland and the Dishonesty of the International Community? - Hilmar Þór HILMARSSON (Revista de Management Comparat International)
The 2008 global crisis hit hard in Iceland. During the crisis its three largest banks all collapsed in just a few days. This article focuses on the actions of the international community when the Icelandic authorities, during a period of great need and uncertainty, sought international assistance to protect the Icelandic economy before the banking system fell. Considering those actions is important because they had consequences not only for Iceland but also for the citizens of other countries. The article also reviews the response of the European Central Bank, the Federal Reserve as well actions of the Nordic countries which Iceland, as the smallest member of that group, sometimes naïvely tends to rely upon for support during difficult times. Was the international community dishonest in its response to Iceland?